Combination of the Systemin peptide with the beneficial fungus Trichoderma afroharzianum T22 improves plant defense responses against pests and diseases. Issue 1 (31st December 2022) - Aprile, Anna Maria; Coppola, Mariangela; Turrà, David; Vitale, Stefania; Cascone, Pasquale; Diretto, Gianfranco; Fiore, Alessia; Castaldi, Valeria; Romanelli, Alessandra; Avitabile, Concetta; Guerrieri, Emilio; Woo, Sheridan Lois; et al.
ABSTRACT: Trichoderma spp . are among the most widely used plant beneficial fungi in agriculture. Its interaction with the plant triggers resistance responses by the activation of Induced Systemic Resistance mediated by Jasmonic acid and Ethylene and/or Systemic Acquired Resistance, which involves Salicylic acid, with the consequent control of a wide range of plant parasites. However, the benefit they can confer to plants may be reduced or nullified by environmental conditions or fungal ecological fitness. A novel approach to enhance their effectiveness in plant defense is to combine them with bioactive molecules including plant-derived compounds. Here, we show that plant treatment with Trichoderma afroharzianum (strain T22) and Systemin, a tomato peptide active in triggering plant defense, confers protection against the fungal pathogens Fusarium oxysporum, Botrytis cinerea and the insect pest Tuta absoluta . The observed defensive response was associated with an increase of Jasmonic acid and related metabolites and a decrease of Salicylic acid.